Rasgos estructurales de la industria local-global del software en Rosario - Pellegrini, José Luis (2019)
This paper presents the first results of a survey of the software industry based in Rosario, which is of interest as a provider of computer solutions for digital multilateral platforms. The character-istics detected allow it to be identified as a local-global industry composed of SMEs and subsid-iaries of larger companies that compete in the global software market.